Problems and Solutions for Literacy Development of 5th Grade Elementary School Students Amidst Covid-19 Pandemic Era in Mandailing Natal Regency - Parulian Ruli Siregar; Suadi Suadi; Rahim Seri Hanida (Jurnal Basicedu, 2021)
Literacy is defined as the ability to listen, speak, read and write. The literacy development of 5th Grade Elementary School students amidst covid-19 pandemic era faces a myriad of problems. Those problems are urgently needed to be solved. The objective of this study is to identify problems and to discover solutions for literacy development of 5th grade elementary school students during covid-19 era pandemic. The data were collected through semi-structured interview involving 23 teachers of 5th elementary school in 23 districts located in Mandailing Natal Regency. The data were afterwards analyzed by thematic analysis with the results distributed into the most specific separated themes. The overall results revealed that 31 problems were found. They were consisting of 8 problems of listening, 8 problems of speaking, 7 problems of reading and 8 problems of writing. Moreover, this study also uncovered 32 solutions for literacy development problems. They were 10 solutions for listening, 6 solutions for speaking, 10 solutions for reading and 6 solutions for writing. These findings could function as significant sources for relevant problem solving in literacy development context amidst covid-19 pandemic era.